(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Non communicable diseases like type 1 diabetes mellitus (DM) are increasing in children. Ten persent of diabetes are type 1. Diabetic nephropathy(DN) and diabetic retinopathy (DR) are the most common complications in DM Diabetic nephropathy is characterized by persistent proteinuria leading to end stage renal disease Around 25-45% of patient with type 1 diabetes will develop overt nephropathy over 10-15 years Hence it is very rare to develop diabetic nephropathy and retinopathy after 2 years of arising symptom in the paediatric age group .In this case report we describe a 15 years old boy who was diagnosed to have type 1 DM 7 days back and symptoms of DM started 2 years back . Patient develop overt nephropathy manifested by edema and proteinuria and retinopathy manifested by dimness of vision, microaneurysm with dot and blot haemorhage after 2 years of complaining symptoms suggestive of DM. The patient was managed accordingly with insulin therapy for tight glycaemic control and supportive therapy for chronic kidney disease (stage IV). As retinopathy preceed nephropathy, so renal biopsy was not done. It is recommended that all children should be screened for type 1 DM periodically to ensure good glycaemic control as well as reduce the complication like DR and DN. J Shaheed Suhrawardy Med Coll, 2014; 6(2):93-95